Long-Term Treatment With Morphine Increases the D-Serine Content in the Rat Brain by Regulating the mRNA and Protein Expressions of Serine Racemase and D-Amino Acid Oxidase - Masanobu Yoshikawa; Takashi Shinomiya; Naoko Takayasu; Hideo Tsukamoto; Mitsuru Kawaguchi; Hiroyuki Kobayashi; Tetsuo Oka; Atsushi Hashimoto (Elsevier, 2008)
Recent studies indicate that an endogenous co-agonist for an N-methyl-D-aspartate (NMDA) receptor-related glycine site, D-serine, is synthesized by serine racemase and is metabolized by D-amino acid oxidase (DAO) and that acute treatment with morphine augments the gene expression of serine racemase and DAO in rat brain. To further elucidate the mechanism underlying the activation of NMDA receptors following chronic opioid administration, we have evaluated the effects of the chronic administration of morphine on the mRNA and protein expressions of serine racemase and DAO and on the contents of D-serine in several areas of the rat brain. Repeated administration of morphine for 30 days produced a significant augmentation of both the mRNA and protein expressions of serine racemase in all the brain regions, whereas no significant change in the protein expression of DAO was observed in all the brain regions. Furthermore, the chronic administration caused a slight but significant elevation in the concentration of D-serine in the cortex, striatum, and hippocampus. These results indicate the elevated D-serine level following the chronic morphine treatment could at least in part be involved in the activation of NMDA receptors via the glycine site. Keywords:: D-serine, serine racemase, D-amino acid oxidase, morphine, N-methyl-D-aspartate receptor